Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1098/rstb.2018.0246
|View full text |Cite
|
Sign up to set email alerts
|

Predictability in the evolution of Orthopteran cardenolide insensitivity

Abstract: The repeated evolutionary specialization of distantly related insects to cardenolide-containing host plants provides a stunning example of parallel adaptation. Hundreds of herbivorous insect species have independently evolved insensitivity to cardenolides, which are potent inhibitors of the alpha-subunit of Na + ,K + -ATPase (ATPα). Previous studies investigating ATPα-mediated cardenolide insensitivity in five insect orders have revealed remarkably high levels of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 74 publications
1
55
0
Order By: Relevance
“…Another transporter of note is the Na + /K + -ATPase pump, the beta 2 subunit expression of which was elevated in chemically defended wild-caught frogs compared with laboratory frogs. The Na + /K + -ATPase pump alpha subunit is a frequent target in the evolution of toxin resistance in a number of herbivorous invertebrates (Yang et al, 2019;Dobler et al, 2012) and vertebrates (Ujvari et al, 2015). Investigations of the function and evolution of the beta subunit in the context of toxin resistance is lacking.…”
Section: Sodium Transportersmentioning
confidence: 99%
“…Another transporter of note is the Na + /K + -ATPase pump, the beta 2 subunit expression of which was elevated in chemically defended wild-caught frogs compared with laboratory frogs. The Na + /K + -ATPase pump alpha subunit is a frequent target in the evolution of toxin resistance in a number of herbivorous invertebrates (Yang et al, 2019;Dobler et al, 2012) and vertebrates (Ujvari et al, 2015). Investigations of the function and evolution of the beta subunit in the context of toxin resistance is lacking.…”
Section: Sodium Transportersmentioning
confidence: 99%
“…Support for this hypothesis comes from the fact that multiple insect species specializing on CGcontaining host-plants have independently duplicated and neofunctionalized ATPa1. In all cases examined to date, species with two or more copies retain one minimally altered copy that is more highly expressed in nervous tissue, and have evolved one or more insensitive copies that are more highly expressed in the gut, the site of absorption of CGs Yang et al 2019). Further support for negative pleiotropic effects is provided by the expression of engineered ATPa1 constructs in cell lines, suggesting that some duplicate-specific CG-insensitivity substitutions appear to reduce NKA activity (Dalla and Dobler 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this wide variety of potential paths to CG-insensitivity, the evolution of insensitivity in most CG-adapted insects is due, at least in part, to target-site insensitivity. Indeed, in most cases, diet specialization on CG-containing hostplants has been accompanied by recurrent adaptive amino acid substitutions to the CG-binding domain of the alpha-subunit of NKA, ATPa1 Dobler et al 2012;Yang et al 2019). Previous studies have identified up to 35 sites in ATPa1 at which substitutions could contribute to CG-insensitivity (reviewed in Zhen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major peak in the elution profile shows acetylcholinesterase activity of 0.280 M/min/ml. This shows considerable elution of the pure enzyme from its crude homogenate under considerable standard conditions [20].…”
Section: Discussionmentioning
confidence: 97%